2014
DOI: 10.1080/10942912.2012.704472
|View full text |Cite|
|
Sign up to set email alerts
|

Silter Cheese, a Traditional Italian Dairy Product: A Source of Feasible Probiotic Strains

Abstract: Silter cheese is a traditional hard cheese, produced in Valcamonica, Brescia, Italy. A total of 426 lactic strains isolated from Silter were analyzed to determine their probiotic characteristics. 274 out of 426 strains were found to produce bacteriocins against at least one of eight different pathogens (Salmonella enterica, Listeria monocytogenes, Salmonella derby, Salmonella thyphimurium, Salmonella napoli, Staphylococcus aureus, E. coli O157:H7, Salmonella enteritidis). In addition, 211 of 274 bactericin-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
(16 reference statements)
0
4
0
1
Order By: Relevance
“…(2011) suggested that lactic acid bacteria are widely distributed in natural fermented foods as indigenous microflora. Also previous studies have been performed to analyze the diversity of the microbial species existing in traditional fermented dairy products in various locations, such as Turkey ( Gurses and Erdogan, 2006 ), Africa ( Mathara et al ., 2004 ), Italy ( Losio et al ., 2014 ), Mongolia ( Takeda et al ., 2013 ), Iran ( Azadnia and Khan Nazer, 2009 ), Morocco ( Ouadghiri et al ., 200 9) etc.…”
Section: Introductionmentioning
confidence: 99%
“…(2011) suggested that lactic acid bacteria are widely distributed in natural fermented foods as indigenous microflora. Also previous studies have been performed to analyze the diversity of the microbial species existing in traditional fermented dairy products in various locations, such as Turkey ( Gurses and Erdogan, 2006 ), Africa ( Mathara et al ., 2004 ), Italy ( Losio et al ., 2014 ), Mongolia ( Takeda et al ., 2013 ), Iran ( Azadnia and Khan Nazer, 2009 ), Morocco ( Ouadghiri et al ., 200 9) etc.…”
Section: Introductionmentioning
confidence: 99%
“…Silter PDO refers to a half-fat hard cheese made with raw milk from cows fed mainly on fodder from the production area. At least 80% of the animals must belong to typical alpine breeds-Grigio Alpina, Pezzata Rossa and Bruna-the latter of which must represent at least 60% of the lactating cows present on each individual farm [2].…”
Section: Introductionmentioning
confidence: 99%
“…Τα τελευταία χρόνια υπάρχει μία αύξηση ενδιαφέροντος για την εμπορική αξιοποίηση των ειδών του γένους Lactobacillusπου έχουν απομονωθεί από παραδοσιακά ζυμούμενα προϊόντα όπως είναι το kefir (Paiva et al, 2016;Zanirati et al, 2015;Wang et al, 2009;), τα λουκάνικα (Diasetal., 2013), το τυρί (Caggia et al, 2015;Losio et al, 2015) L.crispatus, L. amylovarus, L. gallinarum, L. gasseri, L. johnsonii, L. helveticus, L. delbrueckiisubsp. bulgaricus, L. salivariussubsp.…”
Section: το γένος Lactobacillusunclassified